Evaluating the Cost-effectiveness of Catheter Ablation of Atrial Fibrillation - Chang, Andrew Y (Arrhythm Electrophysiol Rev, 2014)
Atrial fibrillation (AF) is one of the most common cardiac conditions treated in primary care and specialty cardiology settings, and is associated with considerable morbidity, mortality and cost. Catheter ablation, typically by electrically isolating the pulmonary veins and surrounding tissue, is more effective at maintaining sinus rhythm than conventional antiarrhythmic drug therapy and is now recommended as first-line therapy. From a value standpoint, the cost-effectiveness of ablation must incorporate the upfront procedural costs and risks with the benefits of longer term improvements in quality of life (QOL) and healthcare utilisation. Here, we present a primer on cost-effectiveness analysis (CEA), review the data on cost-effectiveness of AF ablation and outline key areas for further investigation.